Partisipasi Petani dalam Program Indeks Pertanaman (IP) Padi 400 di Desa Kragan, Kecamatan Gondangrejo, Kabupaten Karanganyar - Sari, Anisa Dyah Talia; Widiyanto, Widiyanto; Anantanyu, Sapja (Universitas Muhammadiyah Semarang, 2024)
The Ministry of Agriculture conducted a program to increase the Rice Planting Index (IP) to 400 or commonly known as the IP400 program. One of the factors determining the success of the Rice Planting Index (IP) 400 program is the participation of farmers in following the program, because without active participation from farmers the program will not run smoothly. This study aims to assess the level of farmer participation, examine the factors that shape farmer participation, and analyze the relationship between the factors that shape farmer participation in the Rice 400 Cropping Index (IP) program in Kragan Village. Sampling was conducted using saturated sampling method (census) with a sample size of 30 respondents. Data analysis used the Spearman Rank Correlation Coefficient Test (rs) at the 95% confidence level. The results showed that the planning stage was in the medium category, while the implementation, utilization of results, and valuation stages were in the high category. The relationship between factors shaping farmer participation in the Rice 400 Planting Index (IP) program is that there is a significant relationship between non-formal education, personal experience of farmers in farming, the influence of people who are considered important, and land area with farmer participation in the IP Rice 400 program. Factors shaping farmer participation in the Rice 400 Planting Index (IP) program that do not have a significant relationship are the age of farmers and formal education of farmers.